Inter and intra-specific diversity in Alternaria species infecting oilseed Brassicas in India - JK Aneja; A Agarwal; A Agnihotri (Journal of Oilseed Brassica, 2026)
The work was initiated to determine diversity in pathogen population of Alternaria blight which results in up to60% yield losses in the world. It is a most prevalent fungal disease of oilseed Brassica in North and North-West regions of India where approximately 80% of Brassicas are grown. Fifty five single spore isolates ofAlternaria species (32 of A. brassicae, 20 of A. brassicicola and 3 of A. alternata) were isolated frominfected leaf samples collected from 8 states of India. The purified isolates were evaluated for theirmorphological, cultural, biochemical and molecular characteristics, and also preserved in DMSO andglycerol. Significant variations (P< 0.05) were observed in sporulation intensity, spore morphology, radialgrowth and carbohydrate concentration among isolates of each species. Analysis of RAPD banding profilesalso showed a high level of genetic diversity varying between 57-78%, 78-92% and 89-100%, among the A.brassicae, A. brassicicola and A. alternata isolates, respectively. Extensive variations were observed inisolates for all the parameters studied, but no correlation could be established. This study, thus indicates thata significant non-specific variation exist between isolates infecting different species and varieties ofBrassica in India. This is the first report of comparative evaluation of the three Alternaria species fromdifferent locations, on three different media and cryopreservation.